Students Water Literacy in South Sumatera Indonesia, Does Indigenous Culture Had Influence? - Meilinda Meilinda; Nazip Khoiron; Riyanto Riyanto; Nike Anggraini; Rendi Restiana Sukardi (JETL (Journal of Education, Teaching and Learning), 2023)
Water literacy, or the culmination of water-related knowledge, attitudes and behaviours, is a relatively new field of study with growing importance for sustainable water management and social water equity (McCarroll & Hamman, 2020). This study aims to analyse students' water literacy from two area in South Sumatera Indonesia, one area is from Semende which is subdistrict of Muara Enim with Indigenous Culture of water conservation and other students came from Palembang Districts which is at the same province with Semende districs, with a similar abundance of water but without Indigenous Culture. This study's samples were 439 respondents, consisting of 184 boys and 255 girls aged 11-18 years from junior and senior high school students in Palembang Municipality and Semende sub-districts of Muara Enim. There were 39 questions for measuring water literacy in the form of a Likert scale (1-5) to assess knowledge, attitude and behaviours in practical and living literacy. Social literacy was measured in the open-ended question instrument. Three of this water literacy was analysed descriptively. The results showed that practical water literacy in Semende and Palembang was significantly different but not with living water literacy. Besides, students' social water literacy in the Semende had two different answer patterns, while, in Palembang, it was more diverse with six different response patterns.